Dielectric and ferroelectric properties of Ta-doped Ba0.7Ca0.3TiO3ceramics - Panupong Jaiban (2018)
© 2017 Elsevier Ltd and Techna Group S.r.l. (Ba 0.7 Ca 0.3 ) 1-x/2 Ti 1-x Ta x O 3 ceramics where x = 0, 0.01, 0.02 and 0.03 were prepared employing a solid state sintering technique. The decrease of tetragonality and the presence of ferroelectric polar clusters in non-polar matrix were induced via Ta doping. The grain size decreased with an increase of Ta addition. The decrease of the phase transition temperature was observed in correlation with the decrease of tetragonality. Depending on Ta content, the normal ferroelectric and relaxor-like behaviors of dielectric and ferroelectric properties were resulted from the dominance of ferroelectric polar clusters and a creation of donor-induced vacancies. The result here suggested that BCT properties may be largely tunable by Ta dopants and could be an attractive material for high-dielectric response devices.